Electrolytic copper foil
By increasing the proportion of vertical columnar crystals in electrolytic copper foils and optimizing surface roughness, the challenge of achieving high flexibility and smoothness after annealing is addressed, resulting in a copper foil suitable for flexible substrates.
Patent Information
- Application Number
- JP2021574617
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2021-01-14
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2041-01-14
AI Technical Summary
Existing electrolytic copper foils used in flexible substrates face challenges in achieving both high flexibility and smoothness after annealing, as they tend to retain higher tensile strength and struggle to control surface roughness within the desired range.
The development of an electrolytic copper foil with a high proportion of vertical columnar crystals, identified through electron beam backscattering diffraction (EBSD), which extends in the foil thickness direction, achieving a ten-point average roughness of 0.1 μm or more and 2.0 μm or less, and a longitudinal crystal ratio of 63% or more.
This approach results in an electrolytic copper foil that exhibits high flexibility, particularly after annealing at 180°C for 1 hour, while maintaining a high degree of smoothness, making it suitable for flexible substrates.
Smart Images

Figure 0007656554000005 
Figure 0007656554000006 
Figure 0007656554000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolytic copper foil, and more particularly to an electrolytic copper foil used for flexible substrates. [Background technology]
[0002] As an electrolytic copper foil for printed wiring boards, copper foil containing as little chlorine as possible (hereinafter referred to as chlorine-free copper foil) is known. For example, Patent Document 1 (JP Patent Publication 2006-52441 A) discloses a copper foil in which the Cl content in untreated copper foil is less than 30 ppm. In addition, Patent Document 2 (JP Patent Publication 7-268678 A) discloses an electrolytic copper foil in which the peak values of the X-ray diffraction intensity of the (111) plane and the (220) plane of the copper foil measured from the electrolytic completion side satisfy a predetermined condition, and discloses that this electrolytic copper foil is manufactured using a copper electrolyte in which the lead ion concentration is controlled to 3 ppm or less, the tin ion concentration is controlled to 6 ppm or less, the chloride ion concentration is controlled to 2 ppm or less, the silicon ion concentration is controlled to 15 ppm or less, the calcium ion concentration is controlled to 30 ppm or less, and the arsenic ion concentration is controlled to 7 ppm or less.
[0003] There is also a known technology that attempts to improve the properties of conventional chlorine-free copper foil by adding a small amount of chloride ions to the copper plating solution during foil manufacturing. For example, Patent Document 3 (JP Patent Publication 2018-178261 A) describes a copper foil having (a) a lightness L* value of 75 to 90 on the side that has not been roughened based on the L*a*b color system, and (b) a tensile strength of 40 kgf / mm 2 More than 55kgf / mm 2 The document discloses an electrolytic copper foil having a low angle grain boundary (LAGB) percentage of less than 7.0% as measured by electron backscatter diffraction (EBSD), and it is preferable that the low angle grain boundary (LAGB) percentage be less than 7.0%. This document also describes a plating solution having a chloride ion concentration of 10 ppm, 15 ppm, or 20 ppm and a current of 60 A / dm in the initial copper plating step. 2 , 70A / dm 2 Or 80A / dm 2 It is described that an electrodeposited copper foil was produced using a current density of 1000 .mu.m. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-52441 A [Patent Document 2] Japanese Patent Application Publication No. 7-268678 [Patent Document 3] JP 2018-178261 A Summary of the Invention
[0005] Unlike copper foils used for rigid substrates, copper foils used for flexible substrates are required to have flexibility that allows them to bend freely under external force. Although chlorine-free copper foils with a certain degree of smoothness and flexibility exist, further improvement in smoothness and flexibility is required. Copper foils generally have the property that their tensile strength decreases and their flexibility increases when annealed, but electrolytic copper foils tend to have relatively high tensile strength after annealing (for example, at 180°C for 1 hour), i.e., poor flexibility, compared to rolled copper foils. Therefore, electrolytic copper foils with significantly lower tensile strength after annealing (i.e., high flexibility) are desired. However, in electrolytic copper foils with a low roughness surface with a ten-point average roughness Rz of 0.1 μm or more and 2.0 μm or less, it is difficult to control the tensile strength after annealing, and it is not easy to achieve both smoothness and flexibility at present.
[0006] The present inventors have now discovered that by increasing the proportion of elongated columnar crystals (hereinafter referred to as elongated crystals) that extend in the foil thickness direction, as identified by cross-sectional analysis using electron backscatter diffraction (EBSD), it is possible to provide an electrolytic copper foil that has a high level of smoothness, with a ten-point average roughness Rz of 0.1 μm or more and 2.0 μm or less, while also exhibiting high flexibility suitable for flexible substrates (particularly high flexibility after annealing at 180° C. for 1 hour).
[0007] Therefore, an object of the present invention is to provide an electrodeposited copper foil that has a high degree of smoothness while also exhibiting high flexibility suitable for flexible substrates (especially high flexibility after annealing at 180°C for 1 hour).
[0008] According to one embodiment of the present invention, there is provided an electrodeposited copper foil having a ten-point average roughness Rz of at least one surface of 0.1 μm or more and 2.0 μm or less, When a cross-sectional analysis is performed using electron backscatter diffraction (EBSD), the area of the observation field occupied by copper crystal grains must satisfy the following conditions: i) (101) oriented; ii) an aspect ratio of 0.500 or less; iii) |sinθ| is 0.001 or more and 0.707 or less, where θ (°) is the angle between the normal to the electrode surface of the electrolytic copper foil and the major axis of the copper crystal grain; and iv) The minor axis length of the crystal as an ellipse is 0.38 μm or less The present invention provides an electrolytic copper foil in which the ratio of the area occupied by copper crystal grains that satisfy all of the above requirements is 63% or more.
[0009] According to another aspect of the present invention, there is provided a flexible substrate comprising the electrolytic copper foil. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a graph showing the relationship between the longitudinal crystal ratio and the post-heat tensile strength of the electrodeposited copper foils obtained in Examples 1 to 11. [Diagram 2] FIG. 1 shows cross-sectional EBSD images (IQ+IPF maps (ND direction)) of the electrodeposited copper foils obtained in Examples 1 to 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] definition In this specification, the "electrode surface" of the electrolytic copper foil refers to the surface that was in contact with the cathode during the production of the electrolytic copper foil. In addition, in this specification, the "deposition surface" of the electrolytic copper foil refers to the surface on which electrolytic copper is deposited during the production of the electrolytic copper foil, i.e., the surface that is not in contact with the cathode.
[0012] electrolytic copper foil The copper foil according to the present invention is an electrolytic copper foil. This electrolytic copper foil has a ten-point average roughness Rz of at least one surface of 0.1 μm to 2.0 μm. When the electrolytic copper foil is analyzed by cross-section electron backscatter diffraction (EBSD), the proportion of the area occupied by copper crystal grains that satisfies all of the following conditions is 63% or more in the area of the observation field occupied by copper crystal grains: i) oriented in (101), ii) aspect ratio of 0.500 or less, iii) |sinθ| is 0.001 to 0.707, where θ(°) is the angle between the normal to the electrode surface of the electrolytic copper foil and the major axis of the copper crystal grain, and iv) the length of the minor axis of the crystal approximated as an ellipse is 0.38 μm or less. In this way, by increasing the proportion of elongated columnar crystals (hereinafter referred to as elongated crystals) that extend in the foil thickness direction, as identified by cross-sectional analysis using EBSD, it is possible to provide an electrolytic copper foil that has a high level of smoothness, with a ten-point average roughness Rz of 0.1 μm to 2.0 μm, while also exhibiting high flexibility suitable for flexible substrates (especially high flexibility after annealing at 180° C. for 1 hour).
[0013] As mentioned above, copper foil generally has a characteristic that its tensile strength decreases and its flexibility increases when annealed. However, compared with rolled copper foil, electrolytic copper foil has a relatively high tensile strength after annealing (for example, at 180°C for 1 hour), i.e., its flexibility tends to be poor. Therefore, electrolytic copper foil with a significantly lower tensile strength after annealing (i.e., high flexibility) is desired. However, in electrolytic copper foil having a low roughness surface with a ten-point average roughness Rz of 0.1 μm or more and 2.0 μm or less, it is difficult to control the tensile strength after annealing, and it is not easy to achieve both smoothness and flexibility at present. In this respect, the electrolytic copper foil of the present invention can advantageously achieve both smoothness and flexibility.
[0014] The electrodeposited copper foil has at least one surface with a ten-point average roughness Rz of preferably 0.1 μm to 2.0 μm, more preferably 0.3 μm to 2.0 μm, even more preferably 0.3 μm to 1.8 μm, particularly preferably 0.6 μm to 1.5 μm, and most preferably 0.6 μm to 1.2 μm. Such an electrodeposited copper foil having a low roughness surface is advantageous in that it has few breakage starting points. In this specification, the "ten-point average roughness Rz" is measured in accordance with JIS-B0601:1982 and corresponds to Rzjis in JIS-B0601:2001.
[0015] It is also preferable that both sides of the electrolytic copper foil have a ten-point average roughness Rz within the above range. That is, the ten-point average roughness Rz of both sides of the electrolytic copper foil is preferably 0.1 μm or more and 2.0 μm or less, more preferably 0.3 μm or more and 2.0 μm or less, even more preferably 0.3 μm or more and 1.8 μm or less, particularly preferably 0.6 μm or more and 1.5 μm or less, and most preferably 0.6 μm or more and 1.2 μm or less. Thus, an electrolytic copper foil having a low roughness surface on both sides is advantageous in that it reduces the starting points of breakage.
[0016] The tensile strength of electrodeposited copper foil in its normal state without annealing is 56kgf / mm 2 More than 65kgf / mm 2 It is preferably less than 57 kgf / mm 2 Over 64kgf / mm 2 Less than 59kgf / mm, more preferably 2 Over 64kgf / mm 2 Less than or equal to 60kgf / mm 2 Over 64kgf / mm 2 The tensile strength of the electrolytic copper foil after annealing at 180°C for 1 hour is 15kgf / mm 2 More than 25kgf / mm 2 It is preferably less than 15 kgf / mm 2 More than 24.5kgf / mm 2 Less than 16kgf / mm, more preferably 2 More than 24.5kgf / mm 2Less than 16 kgf / mm 2 More than 24kgf / mm 2 Within the above range, when the electrolytic copper foil is subjected to a heat history by annealing (for example, at 180°C for 1 hour), it can exhibit high flexibility suitable for a flexible substrate. The tensile strength before and after annealing are both measured at room temperature (for example, 25°C) in accordance with IPC-TM-650.
[0017] When the cross section of the electrodeposited copper foil of the present invention is evaluated, the proportion of elongated columnar crystals (hereinafter referred to as elongated crystals) that extend elongatedly in the foil thickness direction is high. This microstructure rich in elongated crystals contributes to both a high degree of smoothness with a ten-point average roughness Rz of 0.1 μm to 2.0 μm and high flexibility suitable for flexible substrates (especially high flexibility after annealing at 180° C. for 1 hour). When the cross section of the electrodeposited copper foil is analyzed by electron backscatter diffraction (EBSD), the elongated crystals meet the following conditions: i) (101) oriented; ii) an aspect ratio of 0.500 or less; iii) |sinθ| is 0.001 or more and 0.707 or less, where θ (°) is the angle between the normal to the electrode surface of the electrolytic copper foil and the major axis of the copper crystal grain; and iv) The minor axis length of the crystal as an ellipse is 0.38 μm or less are identified as satisfying the following:
[0018] Specifically, in the electrolytic copper foil of the present invention, when a cross-sectional analysis is performed by EBSD, the ratio of the area occupied by copper crystal grains that satisfies all of the above conditions i) to iv) in the area of the observation field (for example, width 10 μm × height 28 μm) occupied by copper crystal grains (i.e., vertical crystal ratio) is 63% or more, more preferably 63% to 90% or less, even more preferably 63% to 85% or less, particularly preferably 63% to 80% or less, and most preferably 63% to 75% or less. Within such a range, both a high level of smoothness with a ten-point average roughness Rz of 0.1 μm to 2.0 μm and high flexibility suitable for flexible substrates (especially high flexibility after annealing at 180 ° C. for 1 hour) can be achieved. At this time, a rectangular area of width × height that satisfies the conditions shown in Table 1 is specified as the observation field in EBSD. [Table 1]
[0019] In addition, when specifying the width in the EBSD observation field, a position 3 μm away from the electrode surface of the copper foil in the thickness direction was set as the reference position P 0 The reason for this (i.e. excluding from the field of view the region up to 3 μm in the thickness direction from the electrode surface of the copper foil) is to ensure an EBSD observation field of view that more representatively reflects the main portion of the copper foil in the thickness direction by excluding the surface region on the side where the copper crystal grains are relatively or excessively fine due to the influence of the cathode (especially its structure) used in manufacturing the electrolytic copper foil.
[0020] The EBSD analysis can be performed by subjecting the electrolytic copper foil to a cross-section polisher (CP) to form a polished cross section, and then performing EBSD analysis of the polished cross section with an observation field of width × height shown in Table 1 using an EBSD device (SUPRA55VP, manufactured by Carl Zeiss) under SEM conditions of Vacc. = 20 kV, Apt. = 60 μm, HC mode, Tilt = 70°, and Scan Phase = Cu.
[0021] The determination of the vertically elongated crystal ratio based on EBSD images can be carried out through the following steps. · Primary extraction based on condition i): In the EBSD image of the observation field, analysis is performed using EBSD analysis software (OIM Analysis 7, manufactured by TSL Solutions Co., Ltd.) to extract crystals oriented in (h, k, l) = (1, 0, 1) (for detailed setting conditions, see the examples described later). In this way, the crystal grain region that satisfies the upper i) condition is extracted. Secondary extraction based on conditions ii), iii) and iv): From the data obtained in the primary extraction, crystals that satisfy all of the following conditions were further extracted: aspect ratio 0.500 or less, long axis inclination |sinθ| 0.001 to 0.707, and short axis length 0.38 μm or less when the crystal grain is approximated as an ellipse (see the examples described later for detailed setting conditions), and the total area (μm 2 ) is obtained as the area of the elongated crystal grain. In this way, the crystal grain region that satisfies the above conditions ii), iii), and iv) is extracted. Calculation of the vertical crystal ratio: The area of the elongated grain obtained by the second extraction, S VC (μm 2 ) and the area of the observation field S OA (μm 2 ) and calculate the ratio of the area of the elongated grains to the area of the copper grains by 100 × S VC / S OA The elongated crystal ratio (%) is calculated using the following formula (for setting conditions, see the Examples section described later).
[0022] The thickness of the electrolytic copper foil is not particularly limited, but is preferably 5 μm to 35 μm, more preferably 7 μm to 35 μm, even more preferably 9 μm to 18 μm, and particularly preferably 12 μm to 18 μm.
[0023] It is preferable that one or both sides of the electrolytic copper foil are subjected to a surface treatment. This surface treatment can be a surface treatment generally performed on electrolytic copper foil. Examples of preferable surface treatments include roughening treatment, rust prevention treatment (e.g., zinc plating treatment, zinc alloy plating treatment such as zinc-nickel alloy treatment), silane coupling agent treatment, etc. In addition, the electrolytic copper foil may be provided in the form of a carrier-attached copper foil.
[0024] Manufacturing method The electrolytic copper foil of the present invention has a copper (Cu) concentration and sulfuric acid (H 2 S.O. 4 The electrolytic deposition can be performed by using a copper electrolyte (aqueous solution) having a copper (C) concentration and a chlorine (Cl) concentration, maintaining the bath temperature (temperature of the aqueous solution) shown in Table 2, and performing electrolytic deposition at a current density shown in Table 2. That is, by satisfying the conditions of the copper electrolyte composition, bath temperature, and current density, a cross-sectional structure having a vertical crystal ratio of 63% or more can be realized, and as a result, an electrolytic copper foil can be produced that has a high degree of smoothness on the deposit surface (or both the deposit surface and the electrode surface) with a ten-point average roughness Rz of 0.1 μm to 2.0 μm, while exhibiting high flexibility suitable for flexible substrates (especially high flexibility after annealing at 180 ° C. for 1 hour). As shown in Table 2, the copper electrolyte used in this manufacturing method is preferably a chlorine-free electrolyte that contains as little chlorine as possible.
[0025] [Table 2] EXAMPLES
[0026] The present invention will now be further illustrated by the following examples.
[0027] Examples 1-11 (1) Manufacturing of electrolytic copper foil A sulfuric acid acid copper sulfate solution (chlorine-free) having the composition shown in Table 4 was used as the copper electrolytic solution, a titanium plate electrode (surface roughness Ra=0.19 μm, conforming to JIS-B0601:1982) was used as the cathode, and a DSA (dimensionally stable anode) was used as the anode. Electrolysis was performed at the bath temperature and current density shown in Table 4 to obtain an electrolytic copper foil having a thickness of 18 μm.
[0028] (2) Evaluation of electrolytic copper foil The obtained electrolytic copper foil was subjected to measurement of ten-point average roughness Rz, cross-sectional analysis by EBSD, and measurement of tensile strength as follows.
[0029] <Measurement of ten-point average roughness Rz> The ten-point average roughness Rz (corresponding to Rzjis in JIS-B0601:2001) of the deposit side of the electrodeposited copper foil was measured using a surface roughness tester (Surfcorder SE-30H, manufactured by Kosaka Laboratory Co., Ltd.) in accordance with JIS-B0601:1982 under the conditions of λc: 0.8 μm, reference length: 0.8 mm, and feed speed: 0.1 mm / s. The results are shown in Table 4.
[0030] <Ratio of elongated crystals / EBSD cross-sectional analysis> Four electrolytic copper foil samples were stacked and bonded together with an adhesive (Loctite (registered trademark), manufactured by Henkel Japan Co., Ltd.), and then an ultraviolet-curable resin was applied to the sample surface as a protective layer. The entire sample was coated with carbon, and then broad argon ion beam cross-section processing (Cross Section Polisher (CP) (registered trademark), manufactured by JEOL Ltd.) (accelerating voltage: 5 kV) was performed for 3 hours to obtain a polished cross section for EBSD measurement. For EBSD observation, carbon coating (1 flash) was performed. EBSD analysis of the polished cross section was performed using an EBSD device (FE-SEM device (SUPRA55VP, manufactured by Carl Zeiss) equipped with an EBSD measurement device (Pegasus, manufactured by Ametech Co., Ltd.)) under SEM conditions of Vacc. = 20 kV, Apt. = 60 μm, HC mode, Tilt = 70 °, and Scan Phase = Cu. The observation field in EBSD was 10 μm wide x 28 μm high (according to the conditions shown in Table 1 above). The EBSD image of the observation field was taken under the following conditions: i) (101) oriented; ii) an aspect ratio of 0.500 or less; iii) |sinθ| is 0.001 or more and 0.707 or less, where θ (°) is the angle between the normal to the electrode surface of the electrolytic copper foil and the major axis of the copper crystal grain; and iv) The minor axis length of the crystal as an ellipse is 0.38 μm or less The area occupied by copper crystal grains satisfying all of the above (hereinafter referred to as the area of elongated crystal grains) was determined through the following primary and secondary extractions.
[0031] · Primary extraction based on condition i) The EBSD image of the observation field was analyzed using EBSD analysis software (OIM Analysis 7, manufactured by TSL Solutions Co., Ltd.), and crystals oriented in (hkl) = (101) were extracted. Specifically, on the OIM Analysis 7 screen, from [Properties] of [All data], [(h,k,l) = (1,0,1)] was selected in [Crystal Orientation], the value of [Deviation] was set to less than 60, and (h,k,l) = (1,0,1) was selected in [Crystal Deviation], and the value of [Deviation] was set to less than 12 to extract [Grain data], i.e., particle data. At this time, the setting conditions of OIM Analysis 7 were as follows. PCO[Copper,0.000,45.000,90.000]<60 AND PCD[Copper,1,0,1,0,0,1]<12
[0032] Secondary extraction based on conditions ii), iii) and iv) From the data extracted as described above, crystals that satisfy all of the following criteria were further extracted: aspect ratio 0.500 or less, long axis inclination |sinθ| 0.001 to 0.707, and short axis length 0.38μm or less when the crystal grain is approximated as an ellipse. The total area of these crystals (μm 2 ) was obtained as the area of the elongated crystal grain. In other words, the setting conditions of OIM Analysis 7 were as shown in Table 3. [Table 3]
[0033] Calculation of the vertical crystal ratio: The area S of the elongated grain obtained through the primary and secondary extractions VC (μm 2 ) and the area of the observation field S OA (μm 2 ) and calculate the ratio of the area of the elongated grains to the area of the copper grains by 100 × S VC / S OAThe elongated crystal ratio (%) was calculated according to the following formula. The results are shown in Table 4.
[0034] <Measurement of normal tensile strength> A test piece was obtained by cutting an unannealed electrolytic copper foil sample to a size of 10 mm x 100 mm. The test piece was set in a measuring device (AGI-1KNM1, manufactured by Shimadzu Corporation), and the normal tensile strength (tensile strength) was measured at room temperature (about 25°C) in accordance with IPC-TM-650 under the conditions of a pulling speed of 50 mm / min and a full-scale test force of 50 N. The results are shown in Table 4.
[0035] <Measurement of tensile strength after heating> After annealing at 180°C for 1 hour, the electrolytic copper foil sample was cut into a size of 10 mm x 100 mm to obtain a test piece. The tensile strength of this test piece was measured under the same conditions as the measurement of the normal tensile strength, and the tensile strength after heating was also measured. The results are shown in Table 4.
[0036] [Table 4]
Claims
1. An electrolytic copper foil having a ten-point average roughness Rz of at least one surface of 0.1 μm or more and 2.0 μm or less, When a cross-sectional analysis is performed by electron backscatter diffraction (EBSD), the area of the observation field occupied by copper crystal grains satisfies the following conditions: i) is oriented in the (101) direction; ii) an aspect ratio of 0.500 or less; iii) |sinθ| is 0.001 or more and 0.707 or less, where θ (°) is the angle between the normal to the electrode surface of the electrolytic copper foil and the major axis of the copper crystal grain; and iv) The length of the minor axis of the crystal as an ellipse is 0.38 μm or less. The proportion of the area of copper crystal grains that satisfy all of the above requirements is 63% or more.
2. The electrolytic copper foil according to claim 1, wherein the ten-point average roughness Rz of both surfaces of the electrolytic copper foil is 0.1 μm or more and 2.0 μm or less.
3. After annealing at 180°C for 1 hour, the tensile strength measured in accordance with IPC-TM-650 is 15 kgf / mm 2 25kgf / mm or more 2 The electrolytic copper foil according to claim 1 or 2, wherein the thickness of the electrolytic copper foil is less than 100 nm.
4. In its normal state without annealing, the tensile strength measured in accordance with IPC-TM-650 is 56 kgf / mm 2 More than 65kgf / mm 2 The electrolytic copper foil according to any one of claims 1 to 3, wherein the electrolytic copper foil has a viscosity of less than 1000 MPa.
5. A flexible substrate comprising the electrolytic copper foil according to any one of claims 1 to 4.
Citation Information
Patent Citations
Electrolytic copper foil for printed circuit board and its production
JP1995268678A
Copper foil, manufacturing method therefor, and tab tape
JP2006052441A
Electrolytic copper foil, and electrical component and battery comprising the same
JP2016160503A
Electrolytic copper foil, electrical parts and batteries containing it
JP2016537514A
Electrodeposited copper foil with low repulsive force, method for production thereof, and use thereof
JP2018178261A
Cited By
Electrolytic copper foil
JPWO2021153257A1